Amine-Functionalized Zeolitic Imidazolate Framework-8 (ZIF-8) Nanocrystals for Adsorption of Radioactive Iodine - Lee, Yu Ri; Do, Xuan Huy; Cho, Kie Yong; Jeong, Keunhong; Baek, Kyung-Youl (AMER CHEMICAL SOC, 2020)
The efficient removal of radioactive iodine (I-2) has drawn worldwide attention because of the severe effects of radiotoxicity on the environment and human health. As a result, efficient porous materials for the capture and safe storage of radioactive iodine are required. In this work, nanoscale zeolitic imidazolate framework-8 (ZIF-8) and its amino-functionalized ZIF-8 derivatives with 3-amino-1,2,4-triazole (Atz), denoted as ZIF8-A, were prepared via postsynthetic modification, and their performance for I-2 removal from n-hexane was investigated. The abundant amine functionalities in the ZIF8-A structure including the primary and secondary amine groups (-NH2 and -NH) and triazole-ring (-C=N-NH-) not only serve as effective adsorption sites but also form strong interactions with I-2 via electron transfer from the nitrogen atom of the ligand to I-2. The adsorption isotherms and the kinetics were well fitted by the Langmuir model and the pseudo-second-order kinetic model, respectively, suggesting a monolayer chemisorption process. ZIF8-A61 achieved an adsorption capacity of more than 870% compared to the pristine ZIF-8. Based on the experimental and computational results, a plausible mechanism for the adsorption of I-2 on ZIF8-A nanocrystals is proposed by considering the host-guest interactions, specifically, those between the amine functional groups and I-2. In addition, the reusability and structural stability of the adsorbents were investigated.
Keywords: METAL-ORGANIC FRAMEWORKS; HIGHLY EFFICIENT; CAPTURE; REMOVAL; MOFS; SORBENTS; HYDROGEN; ZR